The business potential of a novel concept in digital food ordering : market analysis, consumer research and product development in South Karelia - Grzegorz, Ondrej (2022)
The author is assessing the market potential of his novel concept dealing with the digitalisation of professional kitchen processes, supply chain planning and consumer advance ordering. The author investigates the available market and explores consumer behaviour and decision-making in South Karelia, a region in Finland. An integral part of the thesis is a 250 respondents survey of consumer actions, demand, dietary preference and purchase patterns in food ordering and dining-related habits. Another exploratory section is a partial market analysis. As auxiliary fields of market analysis, new product development research and competitor analysis are utilised. The author is trying to identify the most recent drivers in the Finnish restaurant and food service market. There is an attempt to ration and weigh domestic and global trends followed by shifts in demand and supply after 2020 with the concept’s trade capabilities. The author interprets survey findings in contrast to empirical research and secondary data. Regarding his other observations from consumer research, market analysis and product development, the author carefully assessed the business potential of his novel concept in professional kitchen operations and food ordering. The thesis is a precursor to the author’s business plan.